XRBars: Fast and Reliable Multiple Choice Selection by Gaze in XR - Nogueira, João Vitor; Morimoto, Carlos (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences Workshops, 2025)
Web browsing is essential for modern education, supporting everything from self-directed study to academic research. However, traditional web interfaces are designed for keyboards and mice, and touch screens creating accessibility barriers for users with motor impairments. Modern Head-Mounted Displays (HMDs), which lack these conventional input devices but often include eye-tracking technology, make gaze-based interaction in XR a promising alternative due to its immersive experience. For a gaze-based XR web browser to be viable, it must be efficient and provide a good user experience. To this end, this paper proposes XRBars, a system that leverages GazeBars to improve accessibility to online educational resources in XR.